2018
DOI: 10.1016/j.invent.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Long-term telemental health prevention interventions for youth: A rapid review.

Abstract: IntroductionThis rapid review identifies and summarizes the effectiveness of preventative telemental health interventions. It investigates studies conducted between 2010 and 2016 that improve mood and anxiety with long-term follow-up.MethodsA literature search of three major databases was performed by four reviewers. After citation tracing, 3604 studies were discovered, and twenty of these met the inclusion criteria. Data from the papers were abstracted, assessed for quality, and effect sizes were calculated.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…7,8,28 While most internet interventions demonstrate favorable changes in depressed mood, our study did not demonstrate between group differences for mood or functional status. 10 However, this is similar to the phase 2 clinical trial of CATCH-IT, which demonstrated lower cumulative prevalence of depressive episodes, but not between group differences in depressed mood. 38 It is possible the extensive human contact within this trial had an ameliorating effect on mood and strengthened functional status, effectively blurring between group results.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…7,8,28 While most internet interventions demonstrate favorable changes in depressed mood, our study did not demonstrate between group differences for mood or functional status. 10 However, this is similar to the phase 2 clinical trial of CATCH-IT, which demonstrated lower cumulative prevalence of depressive episodes, but not between group differences in depressed mood. 38 It is possible the extensive human contact within this trial had an ameliorating effect on mood and strengthened functional status, effectively blurring between group results.…”
Section: Discussionsupporting
confidence: 73%
“…9 Another review of traditional therapies augmented with computerized communications demonstrated small to moderate effect sizes for depressive symptoms. 10 A systematic review of primary care-based interventions targeting depression identified 14 randomized clinical trials (RCTs); only one included adolescents, and average effect sizes were small. 11 Targeted interventions that show success during trials may not be scalable due to practical issues such as cost, or prove ineffective in the broader community.…”
Section: Introductionmentioning
confidence: 99%
“…TMH held the promise to reach a larger population of youngsters that relies on paediatric or primary care, school, and juvenile correctional populations for their mental health assessment and treatment [ 8 , 17 ]. Overall, the youngsters usually display a greater comfort and satisfaction in receiving a treatment through technology compared to earlier generations, including their parents [ 5 , 17 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have proposed and published the technology-based behavioral vaccine model as an integrated conceptual framework for understanding the prevention of depression across the lifespan through internet-based interventions in community settings [10,29,40]. Based on this model, we propose moderators within this conceptualization: (1) a life course schedule that is theory-driven and that includes booster doses operationalized as patient or participant factors influencing response over the life course, including demographics such as gender, race, ethnicity, age, parental education, and site; vulnerability factors (CES-D10, Adolescent Life Events Questionnaire, Beck Hopelessness Scale, Child Report of Parental Behavior Inventory); child comorbid psychopathology (Child Anxiety Related Emotional Disorders; Disruptive Behaviors Disorder Scale; substance abuse, using CRAFFT [Car, Relax, Alone, Forget, Friends, Trouble]); and parent psychopathology (CES-D10); (2) effective components of information and training to encode responses to future threats that can then be deployed at some future points using information (operationalized as internet modules completed, time on site);…”
Section: Covariates In Moderation Analysesmentioning
confidence: 99%
“…In a review [9] examining 83 studies targeting depressive outcomes in youth, of which 8 were delivered online, only one-third (32/83) specifically focused on reducing the risk of depressive episodes rather than symptoms; small effect size reductions of depressive symptoms were found postintervention, and there was a modest absolute risk reduction of depressive episodes [9]. This limitation, in part, results from a lack of prospective studies examining the long-term outcomes necessary to detect depression onset [7,10]. A prior randomized clinical trial of CATCH-IT [11][12][13], the internet-based depression prevention intervention evaluated in this study, demonstrated lower depressive symptoms at 6, 12, and 30 months, relative to baseline.…”
Section: Introductionmentioning
confidence: 99%